Growth models, growth strategies, and power blocs in Turkey and Egypt in the twenty-first century - Ali Rıza Güngen; Ümit Akçay (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
Analysis of the growth patterns in the Global South in the twenty-first century suggests there is room for authoritarian states to search for new growth models. Authoritarian states, such as Turkey and Egypt, benefited from global financial circumstances in the early 2000s and experienced shifts in growth strategies in the 2010s, suppressing political space further. Our main research question, thus, is focusing on what the main domestic political economy causes of these growth strategy and model changes are. To explain the changes in growth strategies and models amid the strength of reinforced authoritarian regimes in these two countries, we employ a hybrid research strategy, tying growth model changes to conflicts within the power bloc. We argue that in the mid-to-late 2010s, peripheral goods producers gained the upper hand in Turkey, while a military takeover in Egypt was followed by the promotion of exports and new investments. We also contend that power bloc reconfigurations in the last decade and the rise of new growth strategies both in Turkey and in Egypt aimed to change previous domestic demand-led demand and growth models.
Keywords: B52; E65; E66; F43; O43; P52; 330; comparative political economy; growth models; growth strategies; Turkey; Egypt